Pengaruh Lama Perendaman Kolkisin Terhadap Hasil Dan Kualitas Tanaman Jagung Manis (Zea mays L. saccharata) Varietas Paragon - Hadharati Mar`i Rohmita; Mahayu Woro Lestari; Anis Rosyidah (Folium : Jurnal Ilmu Pertanian, 2023)
The demand for sweet corn in Indonesia is increasing along with the increase in population, but national corn production has not been able to meet domestic demand. One of the efforts to improve the quality and quantity of corn productivity can be done by improving plant genetics by artificially increasing ploidy using colchicine. This study aims to determine the effect of different colchicine soaking times and the best colchicine soaking time on the yield and quality of Paragon variety sweet corn (Zea mays L. saccharata). This research was conducted using a simple randomized block design consisting of 6 treatments for 600 ppm colchicine soaking time, namely: R0 = 0 hours, R1 = 5 hours, R2 = 10 hours, R3 = 15 hours, R4 = 20 hours, and R5 = 25 O'clock. Data analysis used the BNJ 5% test. In the observation variable, the number of cobs per plant for the 15 and 20-hour immersion treatments gave the same response as the control treatment. In terms of grain hardness, the treatment with 25 hours of soaking time was a good treatment with a higher hardness value than other treatments. On the character of total dissolved solids, the 25-hour soaking treatment had an effect that reduced plant character. Keywords: colchicine induction, mutation, Zea mays.